ROLE OF NUTRITION IN PSYCHIATRY (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
Nutrition is the science of food and its relationship to health. Psychiatry is the branch of medicine focused on the diagnosis, treatment and prevention of mental, emotional and behavioral disorders. Dietetics as the practical application of the principles of nutrition plays a major role in nutritional neuroscience that deals with the nutritional factors and their correlation to the human cognitive behavior and emotions. Malnutrition has a life-long effect. Malnutrition in early infancy results in decrease in number of neurons resulting in intellectual disability and mental retardation. Psychological manifestations including cognitive inadequacies. People who suffer from a mental health-related pathology have a higher risk to encounter cardiovascular complications that the general population. The psychiatric patients are vulnerable to develop obesity due to sedentary lifestyle, side effects of medication and inability to take care of themselves. This paper looks at the causes of mental disorder which include Biological factors, life experience and environmental factors, psychological and individual factors. Role of nutrition in the prevention of mental health were also discussed. Societal shifts, changes in the typical diet, food insecurity, genetics, nutrition in the prenatal environment, nutrition and stress, energy metabolism and glucose. The roles of major health constituent on mental health were analyzed. Role of vitamins and minerals, neuropsychiatric manifestations due to electrolyte / water disturbance and side effects related to certain nutrient in excess were also discussed. Dietary recommendations were made.